Being a gerontologist: intersections between the professional and the personal in the Ageing of British Gerontology project. Issue 5 (12th May 2021) - Reynolds, Jackie; Bernard, Miriam; Ray, Mo
Abstract: Despite the growth of cultural gerontology this century, relatively few gerontologists have interrogated their own experiences of ageing through a critical reflexive lens. This paper seeks to address this lack of attention by discussing some findings of the Ageing of British Gerontology project: a two-year (2015–2017) Leverhulme-funded study focused on identifying key developments and changes in gerontological research, theory, policy and practice in Britain since the founding of the British Society of Social and Behavioural Gerontology (now the British Society of Gerontology) in 1971. As part of our mixed-method study, we undertook 50 in-depth biographical interviews with 'senior' or retired individuals who have played a key role in the creation and development of gerontology in Britain. As well as focusing more widely on gerontological developments, we asked participants about the relationship between their professional insights into ageing and their personal experiences of ageing – both their own and that of loved ones. In this paper, we discuss the findings in relation to five key themes: health, illness and mortality; close personal relationships; work relationships; challenging ageism; and ageing selves. We found evidence that participants often drew upon their personal experiences of ageing in a range of contexts, including teaching and research. There were also numerous examples of professional insights informing personal decision-making, especially in relation to care of loved ones, though the emotionally challenging aspects of this emphasised the limitations of professional insights. Ultimately, we argue that the distinction between the personal and the professional is something of a false dichotomy, and there is often a complex interplay between the two aspects.